DYNAMIC RESPONSES OF SPRUCE WOOD SANDWICH STRUCTURES UNDER LOW VELOCITY IMPACT TESTS - CHENG JiaJia; HOU ShuJuan (Jixie qiangdu)
As a kind of natural biological material,compared with common metal materials,spruce wood has lighter specific gravity and has the advantages of green,environment-friendly and recyclable. This study took spruce wood as research object,explored the dynamic responses of spruce wood sandwich structures under low velocity impact loadings,compared energy absorption capability of spruce wood sandwich structures with traditional metal sandwich structures,and analyzed the effect of different impact energy and material thickness on its structural deformation process and energy absorption characteristics. The microstructure of spruce wood core was observed with high magnification microscope to analyze how the failure form of core material affect energy absorption characteristics and the relationship between microstructure and macro damage further. The study aims to promote the application of green and environment-friendly materials in body and multi-fields.